Fifty years of Annals of the Faculty of Medicine - Flores Cevallos, Elbio (1989)
Annals of the Faculty of Medicine of the National University of San Marcos has posted just over five decades in almost uninterrupted annual volume; in his early years in bimonthly numbers and in his later years quarterly. 54 volumes until 1971, when it ceased to publish, diverse and complex circumstances were published. In the years when there was a regime Colleges in organizing the Universidad Mayor de San Marcos, it was published under the direction of Dean.